2008
DOI: 10.1016/j.compscitech.2008.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Fracture mechanisms and size effects of brittle metallic foams: In situ compression tests inside SEM

Abstract: a b s t r a c tIn situ compressive tests on specially designed small samples made from brittle metallic foams were accomplished in a loading device equipped in the scanning electron microscopy (SEM). Each of the small samples comprises only several cells in the effective test zone (ETZ), with one major cell in the middle. In such a system one can not only obtain sequential collapse-process images of a single cell and its cell walls with high resolution, but also correlate the detailed failure behaviour of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 42 publications
2
29
0
1
Order By: Relevance
“…The aim is to design specimens, which well reproduce the stress state of the periodic simulations. This approach is similar to the work by Song et al (2008) [6]. In the current paper we treat planar macro-porous ceramics characterized by distributions of closed spherical pores under uniaxial compression, but the idea is in principle also applicable to three-dimensional RVEs.…”
Section: Prediction Of the Breaking Strength Of Macro-porous Materialsmentioning
confidence: 67%
“…The aim is to design specimens, which well reproduce the stress state of the periodic simulations. This approach is similar to the work by Song et al (2008) [6]. In the current paper we treat planar macro-porous ceramics characterized by distributions of closed spherical pores under uniaxial compression, but the idea is in principle also applicable to three-dimensional RVEs.…”
Section: Prediction Of the Breaking Strength Of Macro-porous Materialsmentioning
confidence: 67%
“…Size effect is an important issue in the mechanical testing of metallic foams [19][20][21]. That means the value of the specimen size relative to the mean cell size has great influence on the mechanical properties of the metallic foams.…”
Section: Compression Testmentioning
confidence: 99%
“…A small specimen is required for the observations on the microstructure failure. Song et al [21] found that the failure process of a specimen with insufficient cell is homologous to that of a specimen with many cells. Both of them are defect-directed or weakness-directed processes.…”
Section: Compression Testmentioning
confidence: 99%
“…mechanical, acoustical, thermal, transport-related, … ) of this type of materials strongly depends on their microstructure and this particular link is the subject of an increasing number of studies, for various fields of application, mechanics and acoustics being the most represented. Next to purely experimental studies [5][6][7][8][9][10][11], computational models at the microstructural scale, or homogenization-based and multi-scale models may bring a more in-depth understanding of the relationship between the local morphological features of the material and its global behavior. Closely related to experimental characterizations are the numerical simulations that use the real geometry of materials, thanks to the use of computer-aided tomography data, to build finite element models [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%